Poly(ε-Caprolactone) Nanofibers for Biomedical Scaffolds by High-Rate Alternating Current Electrospinning. Issue 18 (11th April 2016) - Lawson, Caitlin; Sivan, Manikandan; Pokorny, Pavel; Stanishevsky, Andrei; Lukáš, David
ABSTRACT: Poly(ε-caprolactone) (PCL) biopolymer nano- and micro-fibers have been fabricated at high rates up to 14.0 grams per hour using a needleless and collectorless alternating current electrospinning technique. By combining the ac-voltage, glacial acetic acid (AA) as the solvent and sodium acetate (NaAc) as an additive, beadless PCL fibers with diameters tunable from 150 nm to 2000 nm, varying surface morphology and degree of self-bundling were obtained. In this new approach, the addition of NaAc plays a crucial role in improving the spinnability of PCL solution and fiber morphology. NaAc revealed the concentration-dependent effect on charge transfer and rheological properties of the PCL/AA precursor, which results in broader ranges of spinnable PCL concentrations and ac-voltages suitable for rapid manufacturing of PCL-based fibers with different textural properties.